Behavioral and cognitive animal models in headache research - Doga Vuralli; Anne-Sophie Wattiez; Andrew F. Russo; Hayrunnisa Bolay (The Journal of Headache and Pain, 2019)
Abstract Animal models have provided a growing body of information about the pathophysiology of headaches and novel therapeutic targets. In recent years, experiments in awake animals have gained attention as more relevant headache models. Pain can be assessed in animals using behavioral alterations, which includes sensory-discriminative, affective-emotional and cognitive aspects. Spontaneous behavioral alterations such as increased grooming, freezing, eye blinking, wet dog shake and head shake and decreased locomotion, rearing, food or water consumption observed during pain episodes are oftentimes easy to translate into clinical outcomes, but are giving little information about the localization and modality of the pain. Evoked pain response such as tactile and thermal hypersensitivity measures are less translatable but gives more insight into mechanisms of action. Mechanical allodynia is usually assessed with von Frey monofilaments and dynamic aesthesiometer, and thermal allodynia can be evaluated with acetone evaporation test and Hargreaves’ test in animal models. Anxiety and depression are the most frequent comorbid diseases in headache disorders. Anxiety-like behaviors are evaluated with the open-field, elevated plus-maze or light/dark box tests. Interpretation of the latter test is challenging in migraine models, as presence of photophobia or photosensitivity can also be measured in light/dark boxes. Depressive behavior is assessed with the forced-swim or tail suspension tests. The majority of headache patients complain of cognitive symptoms and migraine is associated with poor cognitive performance in clinic-based studies. Cluster headache and tension type headache patients also exhibit a reversible cognitive dysfunction during the headache attacks. However, only a limited number of animal studies have investigated cognitive aspects of headache disorders, which remains a relatively unexplored aspect of these pathologies. Thus, the headache field has an excellent and growing selection of model systems that are likely to yield exciting advances in the future.